1996
DOI: 10.1002/(sici)1096-9861(19960819)372:2<204::aid-cne4>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of cholinergic and GABAergic neurons in the rat medial septum: Different onset of choline acetyltransferase and glutamate decarboxylase mRNA expression

Abstract: In the present study, we have investigated the developmental expression of the transmitter-synthesizing enzymes choline acetyltransferase (ChAT) and glutamate decarboxylase (GAD) in rat medial septal neurons by using in situ hybridization histochemistry. In addition, we have employed immunostaining for ChAT and the calcium-binding protein parvalbumin, known to be contained in septohippocampal GABAergic neurons. A large number of GAD67 mRNA-expressing neurons were already observed in the septal complex on embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…To gain further insight into the neurochemical properties of the differentiated Pax2 cells detected in the septum, we examined co-expression of Pax2 and markers of GABA-ergic and cholinergic neurons, the principal neuronal types of this structure [ 28 - 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…To gain further insight into the neurochemical properties of the differentiated Pax2 cells detected in the septum, we examined co-expression of Pax2 and markers of GABA-ergic and cholinergic neurons, the principal neuronal types of this structure [ 28 - 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…One set of experiments used p75 NTRϪ/Ϫ mice (Lee et al, 1992). During postnatal development in rat, the septohippocampal system acquires the adult pattern at approximately postnatal day 14 (Milner et al, 1983;Linke and Frotscher, 1993;Linke et al, 1995;Bender et al, 1996). Although similar information is limited for mouse Hagg, 1999, 2000;Clancy et al, 2001), it has been reported that the developmental schedule of the mouse CNS precedes that of the rat by ϳ2 d. According to this timetable, the slices used for experiments in this study were derived from mice when the septohippocampal system is in a relatively mature state.…”
Section: Methodsmentioning
confidence: 94%
“…In situ hybridization was performed by using free-floating sections. They were incubated for 10 -18 hr at 47°C in hybridization buffer containing 50% formamide, 4ϫ SSC, 250 g /ml denatured salmon sperm DNA, 100 g /ml yeast tRNA, 5% dextran sulfate, 1ϫ Denhardt's solution (Sigma), and the probe (sense or antisense, diluted 1:1000; Bender et al, 1996). After posthybridization washes (2ϫ SSC for 2 ϫ 15 min at 24°C, 2ϫ SSC /50% formamide for 15 min at 57°C, 0.1 SSC /50% formamide for 15 min at 57°C, and 0.1ϫ SSC for 15 min at 57°C), labeled neurons were detected by a digoxigenin -RNA labeling and detection kit (Boehringer Mannheim, Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%